The effects of casein glycomacropeptide on general health status in children with PKU - Pinto, Alex (2024)
Funding Information: This study was sponsored by Vitaflo International Ltd.\u00AE, UK and Arla Foods Ingredients Group P/S. Publisher Copyright: © 2024